2002
DOI: 10.1007/s00103-002-0483-3
|View full text |Cite
|
Sign up to set email alerts
|

Auswirkungen langfristiger Expositionen gegenüber Straßenverkehrsimissionen auf die Entwicklung von Haut- und Atemwegserkrankungen bei Kindern

Abstract: Effects of long-term exposure to road traffic imissions on the pathogenesis of diseases of the skin and respiratory tract in children Abstract |

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 9 publications
0
5
0
4
Order By: Relevance
“…Increases of cortisol in the first half of the night seem to play an important role. Multiple regression analyses resulted in relative risks of asthma, chronic bronchitis and neurodermitis, which increased significantly with increasing traffic load [17]. A comparison with the literature on such effects caused by air pollution alone showed that traffic noise during the night might have an adjuvant effect on the pathogenesis of the mentioned diseases.…”
Section: Impact Of Noise Levels Over Respiratory Diseases In Childrenmentioning
confidence: 98%
See 2 more Smart Citations
“…Increases of cortisol in the first half of the night seem to play an important role. Multiple regression analyses resulted in relative risks of asthma, chronic bronchitis and neurodermitis, which increased significantly with increasing traffic load [17]. A comparison with the literature on such effects caused by air pollution alone showed that traffic noise during the night might have an adjuvant effect on the pathogenesis of the mentioned diseases.…”
Section: Impact Of Noise Levels Over Respiratory Diseases In Childrenmentioning
confidence: 98%
“…In children, noise interferes in complex task performance, modifies social behavior and causes annoyances; chronic aircraft noise exposure impairs reading comprehension and long-term memory and may be associated with raised blood pressure [85]. Recently, researchers have found a correlation of respiratory diseases to traffic related air pollution and noise [16,17,18], in these studies children under high noise exposure (54-70 dB (A)) had in comparison to all other children significantly increased morning saliva cortisol concentrations, indicating an activation of the hypothalamuspituitary-adrenal (HPA) axis and this leads in the long term to an aggravation of bronchitis. The pathogenesis of allergies can be stimulated by adjuvant effects, air pollutants such as NO 2 and particles from diesel exhaust as previously commented and noise, as well, specially during night time.…”
Section: Impact Of Noise Levels Over Respiratory Diseases In Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the associations indicating the short-term effects of exposure to high noise levels are not spurious and are related to increased blood cortisol levels. This hormone is released during stress reactions, and a relationship between elevated cortisol levels and increased risks of asthma, chronic bronchitis and neurodermitis, which in turn increase with increasing traffic volume [9], has been shown. @ERSpublications First description of the novel association between traffic noise and respiratory mortality, independent of air pollution http://ow.ly/rFAjz…”
Section: Does Traffic Noise Influence Respiratory Mortality?mentioning
confidence: 99%
“…Ein solcher Zusammenhang bestätigte sich in der nachfolgenden Studie allerdings nicht mehr[]. Eine Studie in Arztpraxen aus dem Harz fand einen positiven Zusammenhang mit Neurodermitis[8]. Eine Atopie wurde in 4 Studien auf ihren Zusammenhang mit der Verkehrsbelastung überprüft.…”
unclassified